UPAYA MENINGKATKAN MINAT DAN PEMAHAMAN SISWA PADA MATA PELAJARAN MATEMATIKA DENGAN THINK PAIR AND SHARE ( TPS ) - Widiyanti Widiyanti; Joko Purwanto; Ahmad Ahmad (Khazanah Pendidikan, 2009)
This action research is aimed at improving the student’s interest and achievement in mathematics on the topic of flat plane using think pair share (TPS). The subject of this research were 36 students of grade 7, of Muhammadiyah Junior High School of Sumbang. This is a classroom action research with three cycles each of which consisted of planning, acting, observing, evaluating, and reflecting. The data was collected using questionnaire, observation a\, and test. The result was that the mean of student’s interest was 39.97 in cycle 1 and using observation sheet the mean score is 16.67%. The mean of the students’ achievement. The result in student’s interest in cycle 2 was 47.71 and the result with observation sheet was 17.78%. The students’ achievement mean was 67.56. The research result on student’s interest in cycle 3 was 48.94 and using observation sheet the mean percentage was23.89%. The mean of the students’ achievement was 70.54%. The conclusion was that TPS could improve the students interest and achievement in mathematics. Key words: interest, achievement, think pair share